Perioperative care of people with dementia. (2nd February 2020) - Proc, Jennifer L; Jordan, Helen; Docherty, Annemarie B
Abstract : As the population ages, there is a higher prevalence of both dementia and conditions that require major surgery. However, patients with dementia undergoing surgery have poorer outcomes than surgical patients without dementia. This article explores new guidance about delivering perioperative care for patients with dementia presenting for surgery. Management of patients with cognitive changes begins with developing an understanding of the classifications and pathophysiology of these disease processes, and addressing any modifiable risk factors for developing dementia, postoperative cognitive decline and postoperative delirium. Thorough preoperative assessment provides the opportunity to identify patients with and at risk of these cognitive impairments and to involve the appropriate multidisciplinary team in care planning. Once patients are identified, an individualised perioperative management plan addressing any issues surrounding capacity and consent, conduct of anaesthesia, possible polypharmacy and potential drug interactions, and postoperative pain management can improve quality of care and outcomes for these patients.